The Tax-adjusted Q Model with Intangible Assets : Theory and Evidence from Temporary Investment Tax Incentives - Chen, Sophia (IMF Working Papers; Working Paper ;, 2014)
We propose a tax-adjusted q model with physical and intangible assets and estimate it with a self-collected comprehensive database of intangible assets. The presence of intangibles changes the accounting and economic measures of q. We show that when tax changes are temporary, the q model can be estimated by adjusting for the firm's intangible stock and intangible intensity. We estimate our model using temporary investment tax incentive policies in the United States in the early 2000s. When the q-model accounts for intangible assets, the estimated investment elasticity to tax incentives is generally larger than otherwise. It is also larger for intangible-intensive firms, and increases with firm size.